HUMAN RESOURCES INVESTMENT AND ECONOMIC GROWTH IN INDONESIA - Hismendi; Maulizar; Safaruddin (CV. Radja Publika, 2023)
Increasing government spending on education is closely related to efforts to strengthen human resources in order to encourage national economic growth. Which of the magnitude of the government event for education every year. Many studies prove that there is a relationship between government and education on economic growth. Education has a role in economic development, through the availability of reliable human resources. This study examines the study of the relationship of education to growth. Granger's Causality Model explains the relationship between education spending and economic growth. The results of the study indicate that there is a relationship between education spending on economic growth in Indonesia. demands maximum education expenditure efforts, especially direct challenges to improving human resources. so that an increase in economic growth can be realized in the future.